Vers une modernisation de la gouvernance dans les musées nationaux : théories, pratiques et perspectives - Larocque, Annie-Claude (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2021)
On December 9, 2016, Luc Fortin, Minister of Culture and Communications, announced the adoption of Bill 114, whose goal is to “modernize the governance structure of Quebec’s national museums.” Thirty-three years after the passage of the National Museums Act establishing the Musée national des beaux-arts du Québec (MNBAQ), the Musée d’art contemporain de Montréal (MAC) and the Musée de la civilisation (MCQ) as national museums, the adoption of Bill 114 is an ideal time to examine the concept of governance in the museal context, as well as potential consequences for Quebec museology.While the question of governance has often been raised over the past few years in the field of both public and private administration in Quebec, its application in the domain of museology has long been delayed. Developed structurally and conceptually in the vast majority of the province’s museal network, which is to say that it refers, first and foremost, to a structure of functioning and a management mode, the notion of governance nonetheless generates even more questions about the articulation and comprehension of these principles in regards to their application. In particular, think of the regulations governing the composition of boards of directors, of the criteria for independence which members must observe, of the desired skills profiles, as well as the distribution of roles among the general management and the board of directors.This summary of a directed study submitted in August 2017, seeks to return to the major analyses that have answered this question: after the bill was passed, what organizational dynamics were observed within the MNBAQ, MAC and MCQ?